2007
DOI: 10.1038/sj.sc.3102053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of fatigue in spinal cord injury

Abstract: Study design: Retrospective chart review. Objectives: To determine the prevalence of fatigue in an outpatient spinal cord injury population and to examine the clinical variables contributing to that fatigue. Setting: GF Strong Rehabilitation Centre, Vancouver, British Columbia, Canada. Methods: Medical charts of 76 individuals admitted to the GF Strong Outpatient SCI Program between December 2004 and December 2005 were reviewed. Data collected included information on clinical characteristics, demographics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 16 publications
7
84
3
Order By: Relevance
“…In previous studies, some of the above mentioned variables have shown relationships to fatigue. [8][9][10] As previously mentioned, the variability of findings among studies may be related to methodological differences, and need further clarification.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In previous studies, some of the above mentioned variables have shown relationships to fatigue. [8][9][10] As previously mentioned, the variability of findings among studies may be related to methodological differences, and need further clarification.…”
Section: Discussionmentioning
confidence: 94%
“…24 These variables were selected based on judgement and previous research. [8][9][10] Collinearity problems were indicated if the variance inflation factor for any covariate exceeded five, and by Spearman correlations. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,1,[3][4][5][6][7] Other studies focus on the importance of related symptoms such as pain, psychosocial problems and loss of energy in the rehabilitation patient or the compliance of the patient is seen as a main outcome factor. [8][9][10][11][12][13][14][15][16][17] Studies researching the social reintegration mainly focus on occupational situation, living conditions and quality of life. [18][19][20][21][22][23][24] A multi-dimensionally measuring test device, internationally usable and applicable for inpatients as well as outpatients is thereby currently lacking.…”
Section: Introductionmentioning
confidence: 99%